The Estimation of Total Expected Medical Cost for Heart Disease based on Four Major Illnesses: Angina, Heart Failure, Ischemic and Myocardial Infarction - Ishak, Azril; Nadirah Mohd Johari, Sarah; Idham Mohamad, Arwin; Hanafi Tumin ASA, Mohd (International Journal of Engineering and Technology, 2018)
Ischemic Heart Disease is the number one killer in Malaysia and the total number of death has increased statistically. To make matters worse, the cost of medical related to this disease has increased approximately from 10 percent to 15 percent every year. Therefore, it is crucial to know the expected medical cost of heart disease and the risk exposure. This paper discussed on four different type of major illness relating to heart disease and the expected cost of procedure based on type of illness and age. The objectives are to analyse percentage of people getting heart disease based on age, gender and ethnic, calculation of the probability of four major categories of illness in heart disease and to estimate the total expected cost of heart disease. The result showed the expected cost of heart disease varies based on the cost of procedures and the severity of the heart disease of the patient; the higher the rate of severity, the higher the expected cost would be.Â